Management of Overdenture in a Case of Partial Maxillary Tooth Loss and Complete Mandibular Tooth Loss - Tahta Danifatis Sunnah; Patria Legawa Anggadinata; Rasmi Rikmasari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Extensive tooth loss may impair masticatory function, esthetics, and quality of life, and can accelerate alveolar bone resorption. Overdentures represent a prosthodontic treatment option that preserves remaining teeth or root remnants as supporting structures, thereby improving prosthesis stability and maintaining the supporting tissues.Objective: To report the management of extensive tooth loss using tooth- and root-supported overdentures, with consideration of clinical conditions and patient preferences.Case Report: A 53-year-old male patient presented with a chief complaint of difficulty in mastication due to extensive tooth loss in the maxillary and mandibular arches. Clinical and radiographic examinations revealed the presence of several teeth and root remnants with periodontal conditions that were still suitable for preservation. The treatment was performed in stages, including periodontal and endodontic therapy, extraction of teeth with poor prognosis, and prosthodontic rehabilitation using removable partial dentures combined with bare-root overdentures and non-retentive short coping overdentures.Results: After prosthesis insertion, the patient demonstrated improved masticatory function, comfort, and overall satisfaction. Clinical evaluation showed good adaptation, retention, and stability of the overdentures, with no complaints of pain or soft tissue irritation.Conclusion: Tooth- and root-supported overdentures are an effective treatment option for patients with extensive tooth loss when suitable abutments remain. This approach provides favorable functional and psychological outcomes when supported by appropriate preliminary treatment and regular maintenance.